The Impact of Instructional Transition on Grade 4 Learners’ Academic Engagement: Mother Tongue to English, South African Perspective - Zine Njebedulana; Shakespear Maliketi Chiphambo (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2025)
Teaching English as a medium of instruction in South Africa remains a contentious issue. This research investigated the consequences of using English as a medium of instruction on the academic participation of grade 4 learners. In this instance, Bourdieu’s Theory of Practice was applicable as it considers how a learner's social background and identity influence their learning processes. The study was qualitative and framed within the case study design. Participants were five purposively sampled learners for the semi-structured interviews and 70 for the mathematics lesson observations. The collected data was analysed thematically. Learners could not follow basic English instructions, ask questions, communicate, discuss tasks, answer mathematically posed questions or participate in informal group discussions. The teachers used code-switching, the banking teaching method, and chalkboard and chalk as the materials and resources for teaching. Moreover, more than two learners used single textbooks. Thus, we propose the following: specialised English assistance programmes which improve learners' skills, interactive pedagogic approaches that enhance learners' involvement and participation in English lessons, and incorporation of multimedia, modern technologies and interactive devices to make learning more interesting and relevant, as well as enabling learners to work autonomously and at their own pace, so they can build their confidence towards using English. The Department of Education needs to reduce the size of classrooms for effective teaching and learning and to provide teachers with training on language teaching methods and techniques.